6a-7= 53
You want to get a by itself. Because A is a loner and doesn't want anybody else on his side of the equal sign.
SADMEP
Subtract, add, divide, multiply, exponent, parenthesis.
This is the order of operation you use to any variable by itself.
So in 6a - 7 = 53 the first step you want to do is add 7 to both sides.
1: 6a - 7 + 7 = 53 + 7
The negative and positive 7 cancel out on the left side. So you are left with: 6a = 60
2: divide both sides by 6
6a \ 6 = 60/6
The 6 on the left hand side cancel out. So you are left with a = 60/6
3: simplify. a = 6